2014
DOI: 10.3402/qhw.v9.24105
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff's actions during older residents’ transition into long-term care facility in a nursing home in rural Norway

Abstract: Working in long-term care units poses particular staff challenges as these facilities are expected to provide services for seriously ill residents and give help in a homelike atmosphere. Licensed and unlicensed personnel work together in these surroundings, and their contributions may ease or inhibit a smooth transition for recently admitted residents. The aim of the study was to describe and explore different nursing staff's actions during the initial transition period for older people into a long-term care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…Jacobsen [42] also found that the assistants were a “fellowship of those who have no say” (p 86). For instance, during meals [20] with many cognitively able residents the local staff’s involvement with the new residents could shut the weekend supply staff off from participation. The enthusiastic allies were good at what they were doing and the supply staff could feel redundant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobsen [42] also found that the assistants were a “fellowship of those who have no say” (p 86). For instance, during meals [20] with many cognitively able residents the local staff’s involvement with the new residents could shut the weekend supply staff off from participation. The enthusiastic allies were good at what they were doing and the supply staff could feel redundant.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the dynamic interactions between all the staff suggest the strong interdependence among them. In our previous study [20], the task of writing the handwritten care plans was delegated to the primary auxiliaries to be performed shortly after the new resident had arrived. This indicate that the nurses supported the auxiliaries’ independent contributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for an ILP is due to several factors, but mainly by the lack of support from family members in the care binomial/assistance to that old or the option of the elderly, due to external factors such as loneliness, urban violence, family exclusion and the possibility of being cared for by a team [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of situation creates vulnerability, increase in diseases linked to the immune system, depression, anxiety and suicidal thoughts [14][15][16].…”
Section: Discussionmentioning
confidence: 99%